TANJUNG LAPIN BEACH TOURISM DESTINATION FACILITIES TANJUNG PUNAK VILLAGE RUPAT UTARA DISTRICT BENGKALIS REGENCY RIAU PROVINCE - Reyna Syahanaz; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine of tourism object facilities at Tanjung Lapin Beach. There has been no significant change in the development of Tanjung Lapin Beach tourism object facilities. The purpose of the researchers was to find out how the management of facilities and the constraints experienced in managing the Tanjung Lapin Beach tourism object facilities were used to manage tourist attraction facilities according to (Muklas, 2008) from the main facilities, supporting facilities and supporting facilities. The research method used is qualitative research with data collection techniques namely interviews, observation, and documentation. The results of the study can be concluded that the management of Tanjung Lapin Beach tourism object facilities is adequate, but there are still many facilities that are not optimal and should be realized by the Tanjung Lapin Beach tourism object manager. The inhibiting factors include the limited budget funds provided by the government. It is necessary to make improvements and realize the programs that have been designed such as the management and development of Tanjung Lapin Beach tourism object facilities. Keywords : Facility, Destination, Tanjung Lapin Beach